Psychology Publications by Professors at Argentine Psychology Programs: 1958-1982 - Piñeda, María Andrea (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
From a historiographic standpoint, a description of the research and publications produced by Professors at Argentine National Universities during the foundational ages of Psychology Programs was made. The analysis included institutional, political and social issues. The work involved archives and bibliography tracing, and it focused on Professors publications. Four Psychology Programs at National Universities were especially analyzed: University of Buenos Aires, National University of Cuyo / San Luis, National University of La Plata and National University of Córdoba. Their Professors’ staffs in the period 1957 and 1982 were historically reconstructed, and their psychology publications (journal articles and books) between 1958 and 1982 were traced. Publications were analyzed with bibliometric approach to get a first description, taking into account: relation between Professors / authors, general productivity, publications features: language, nationality, publishing house, journals and publishing houses productivity, research areas and theoretical approaches.